Penerapan Project-Based Learning melalui Pengembangan Alat Filter Udara Berbasis Karbon Aktif dan Arduino sebagai Solusi Masalah Lingkungan - Iin Inayah; Tantri Rahmayu; Halwa Anisa Zaitun (Jurnal Pendidikan dan Ilmu Fisika, 2026)
Air pollution caused by cigarette smoke and vehicle emissions poses serious health risks and provides a meaningful context for project-based learning. This study aimed to describe the implementation of Project-Based Learning (PjBL) through the development of an activated carbon- and Arduino-based air filter and to examine its contribution to students' critical thinking and problem-solving skills. A qualitative descriptive case study was conducted following engineering-based PjBL stages, including problem identification, prototype construction, testing, redesign, and product presentation. Data were collected using PjBL implementation observation sheets, product quality assessment rubrics, and oral communication rubrics. Students developed a prototype incorporating activated carbon, an MQ-135 air quality sensor, a DC fan, and an Arduino Uno. Initial testing revealed limitations in sensor stability, filtration efficiency, and structural strength. These issues were addressed through iterative redesign by improving the filter material, reinforcing the frame, and adding a magnetic locking mechanism. The final prototype demonstrated improved performance, stability, and design quality. Descriptive statistics indicated that PjBL was effectively implemented and promoted students' critical thinking and problem-solving skills through authentic, context-based engineering experiences.